Enhancing Students English Proficiency Through Experiential Learning - Anisa, Ike (International Journal of Active Learning, 2016)
In teaching English the method which is used should be communicative and suited to the students characteristics. It is aimed to create the teaching learning process which is interesting and comforting to the students so that they can reach the learning goal and English becomes a more attractive subject for them. From the reason above, experiential learning method could be as the solution. Experiential learning method can be used in teaching English to make the teaching learning process much interesting and fun. It will enhance students interest in learning process in the classroom, because the circumstances become more interesting. It is suitable with the students who are like to be active so experiential learning can be helpful in teaching English. Experiential learning is so effective to enhance the students English proficiency because its a process of learning by doing. Experiential learning is also a fun way to learn life skills. The students will have fun while they learn and this makes learning more effective and long lasting.How to CiteAnisa, I. (2016). Enhancing Students English Proficiency Through Experiential learning. International Journal of Active Learning, 1(1).